2017
DOI: 10.1111/acem.13214
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Impact of Physician Implicit Racial Bias on Clinical Decision Making

Abstract: The current literature indicates that although many physicians, regardless of specialty, demonstrate an implicit preference for white people, this bias does not appear to impact their clinical decision making. Further studies on the impact of implicit racial bias on racial disparities in ED treatment are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
267
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(278 citation statements)
references
References 36 publications
8
267
0
3
Order By: Relevance
“…The issue of race in general medical decision-making remains contentious, but has not been explored in ICU admission decisions. [10] Race is not recorded on our referral forms. We nevertheless attempted to evaluate race as a factor in this study by ascribing race status according to patient names.…”
Section: Researchmentioning
confidence: 99%
“…The issue of race in general medical decision-making remains contentious, but has not been explored in ICU admission decisions. [10] Race is not recorded on our referral forms. We nevertheless attempted to evaluate race as a factor in this study by ascribing race status according to patient names.…”
Section: Researchmentioning
confidence: 99%
“…Early identification and timely treatment of critical cases of SARS-CoV-2 is vital for reducing disease severity and preventing spread 21 , so biases in care could have significant consequences. It is important to note that the literature is divided upon whether or not implicit biases of clinicians translate to different treatment recommendations or care 124,125,126 , though existing studies generally confirm an implicit preference for NHWs over Blacks 127,128,129 . Efforts to treat without acknowledging race or ethnicity (i.e.…”
Section: Racism and Discrimination In Medical Carementioning
confidence: 99%
“…Although a prowhite bias has been demonstrated as the norm in numerous studies, the effects of this bias on outcomes and clinical decision making are unclear. A recent systematic review by Dehon and colleagues included studies that evaluated implicit bias and clinical decision making. The results indicate that although there is a prowhite bias among physicians, none of the nine studies reviewed found bias to have an impact on clinical decision making …”
Section: Introductionmentioning
confidence: 99%